Neurophysiological mechanisms of functional bandage application in somatosensory stimulation - Zavarize, Sergio Fernando (2014)
Kinesio Taping (KT) is a method of elastic bandage which favors the stimulation of the tegumentary system via somato-sensorial receptors. The maintenance of a particular body orientation is obtained from the complex relationship between sensory information and muscular activity. tegumentary system. In this sense, the KT assists in therapy by means of constant and enduring mechanical stimuli in the skin which by action of mechanoreceptors are a neural arch and contribute to the perception of body position and joint movement. This review is a description of the neuro-physiological mechanisms of applying bandages KT in stimulating the somatosensory receptors pointing its therapeutic actions in using this method. The survey was conducted from a bibliographic review of specialized literature, being consulted scientific articles located in the databases Medline, Scielo, Lilacs and in the CAPES Journal Portal and additionally the academic books query to search for  complements of the research, published between 1999 to 2013, as well as cross-references to articles selected. The KT is an innovative technique that was created specifically to treat orthopedic injuries caused by sport and further research are being carried out aiming at the beneficial effects of their use for therapeutic purposes in the rehabilitation of different types of pathologies.